Developing student's historical consciousness by understanding the indonesian history and the historical thinking. (March 2019) - Ramdhani, A M; Naim, M.; Sumardi,
Abstract: This research to analyze the relationship between understanding Indonesian history and the historical thinking with student's historical consciousness. The Ex-postfacto is the type of this research with correlational research design.. The population of this research was Senior High School Students in Jember. Random sampling technique was used as a method to take the sample. The instruments used were documents and questionnaire. The analysis data was conducted by using correlation analysis and multiple linear regressions. The result showed that there is a positive relationship as well as the improving significantly between understanding the Indonesian history and the students' historical thinking with students' historical consciousness, with 5% of significance and 60, 1 of its contributions. It showed that the understanding the Indonesian history and students' historcial thinking is able to improve the students' historical consciousness